HUBUNGAN KEJADIAN PREEKLAMPSIA DENGAN KEJADIAN ASFIKSIA NEONATORUM DI RSUD WATES KULON PROGO - Irawati, Yuli; Margono, Margono; Estiwidani, Dwiana (Jurnal Kesehatan Ibu dan Anak, 2012)
The highest maternal mortality in Indonesia was caused by obstetric complications (90%) that was bleeding (30.77%) infection (22.5%), preeclampsia and eclampsia (25.18%), others (11. 55%). Pre-eclampsia can be changes in the placenta which decreased blood flow to the placenta resulting in placental dysfunction. At one moment preeclampsia impaired fetal growth, whereas the shorter pre-eclampsia can occur until the death of fetal distress from lack of oxygen (hypoxia) and at delivery is the greater danger, babies often show signs of postpartum neonatal asphyxia due to intrauterine hypoxia. Objectives: Knowing the relationship of preeclampsia incident with asphyxia neonatorum incident of Wates hospital in 2011.This was an observational analytic study that used historical cohort design, independent variable was incidence of preeclampsia and dependent variable was incidence of asphyxia neonatorum. Overall population of mothers in childbirth in hospitals Wates began in January 2009 to December2010. The sample size was ,30 subjects exposed (preeclampsia) and 130 unexposed subjects (not preeclampsia). Data analyzed using Chi Square, percentages, and relative risk. Results showed there was relationship between the incidence of preeclampsia with asphyxia neonatorum with a value of p = 0.04. The incidence of asphyxia neonatorum in preeclampsia women lot of 45 people (35%), incidence of asphyxia neonatorum without preeclamptic women lot of 30 people (23%). Relative Risk (RR) obtained at 1 .7 with 95% Cl (0.23-3.043).